Discrimination of atypical atrioventricular nodal reentrant tachycardia from atrial tachycardia by the V‐A‐A‐V response. Issue 7 (13th June 2022) - Kaneko, Yoshiaki; Nakajima, Tadashi; Tamura, Shuntaro; Nagashima, Koichi; Kobari, Takashi; Hasegawa, Hiroshi; Ishii, Hideki
Abstract: Introduction: The electrophysiological discrimination between fast‐slow (F/S‐) atrioventricular (AV) nodal reentrant tachycardia (NRT) and atrial tachycardia (AT) originating from the interatrial septum remains challenging. While a V‐A‐A‐V response may occur immediately after ventricular induction or entrainment of either tachycardia, the electrophysiological dissimilarities in that response between the two tachycardias remain unclear. The purpose of this study was to identify a diagnostic indicator discriminating F/S‐AVNRT from AT by examining the difference in the V‐A‐A‐V response between the two tachycardias. Methods: This retrospective study included 17 patients with F/S‐AVNRT [seven with common‐form F/S‐AVNRT using a typical slow pathway (SP) and 10 with superior type F/S‐AVNRT using a superior SP] and 10 patients with reentrant AT. All 27 patients presented with long RP supraventricular tachycardia and an initial V‐A‐A‐V response upon ventricular induction or entrainment. The V‐A‐A‐V response in patients with F/S‐AVNRT was due to dual atrial responses. We measured the interval between the first (A1) and second atrial electrogram (A2) of V‐A‐A‐V and calculated ΔAA by subtracting A1‐A2 from the tachycardia cycle length. Results: V‐A‐A‐V responses were observed most often upon ventricular induction of F/S‐AVNRT (6 ± 5 times) as well as AT (6 ± 6 times; p  = .87). The V‐A‐A‐V response upon ventricular entrainment was observed in a single patient with F/S‐AVNRT versus 10 all patients with AT ( p  < .001). ΔAA ranged between −80 and 228 ms in F/S‐AVNRT and between −184 and 26 ms in AT. A ΔAA > 26 ms predicted a diagnosis of F/S‐AVNRT with a 76% sensitivity and 100% specificity, while a ΔAA <−80 ms predicted a diagnosis of AT with a 50% sensitivity and 100% specificity. Conclusions: ΔAA is a useful, confirmatory, diagnostic indicator of F/S‐AVNRT versus AT associated with the V‐A‐A‐V response.